Investigation of adsorption and biosorption features of bio-functionalized poly(GMA-Co-EGDMA) polymer beads in the treatment of nicotine from tobacco industry - Simsek, Esra Bilgin; Saloglu, Didem; Aydın, Ahmet Alper (Springer Science and Business Media LLC, 2023)
The investigation of multifunctional materials for modern enzyme immobilization is an attractive subject in advanced adsorption and biosorption applications. In the present study, the feasibility of immobilization of Lipozyme TL 100L (LPZM) on 3-aminopropyltriethoxysilane (APTES) modified poly-(GMA-co-EGDMA) (PEGDMA) was investigated for adsorption and biosorption of nicotine from aqueous solution. Characterization tests confirmed successful immobilization of lipozyme which significantly altered thermal behavior, surface characteristics, and surface morphology of PEGDMA and PEGDMA/APTES. In addition, the immobilization yields were calculated as 85.0% and 72.0% onto PEGDMA/APTES using physical adsorption and covalent immobilization methods, respectively. The nicotine removal efficiencies were calculated to be 66.4%, 79.0%, 98.9%, and 85.7%, using raw PEGDMA, PEGDMA/APTES, PEGDMA/APTES@LPZM, and PEGDMA/APTES/GU@LPZM, respectively. For the raw PEGDMA, the Langmuir isotherm was best fitted to the adsorption data, while Langmuir-Freundich model described well the adsorption process on PEGDMA/APTES and PEGDMA/APTES@LPZM. The maximum adsorption capacities of Langmuir-Freundlich model increased from 8.118 to 17.32 mg/g after enzyme immobilization. The negative enthalpy value, ΔH° (- 10.37 kJ/mol), revealed that the nicotine adsorption on PEGDMA/APTES@LPZM was exothermic in nature, which was corroborated by the decrease observed in the number of adsorbed molecules with increasing temperature. In the kinetic experiments, the adsorption on PEGDMA and PEGDMA/APTES@LPZM reached equilibrium with the removal percentages as 66.4% and 98.9% at the end of 3 h, respectively. The nicotine adsorption performances in real water matrices were also investigated, and PEGDMA/APTES@LPZM showed satisfactory reusability with removal percentage decreased from 98.9% (1st cycle) to 83.0% (6th cycle).
Keywords: Nicotine; Kinetics; Polymers; Thermodynamics; Tobacco Industry; Adsorption; Hydrogen-Ion Concentration; Enzymes, Immobilized; Water Pollutants, Chemical